A girl is a body of water - Makumbi, Jennifer Nansubuga (Portland, Oregon Tin House, 2020)
n her twelfth year, Kirabo, a young Ugandan girl, confronts a piercing question that has haunted her childhood: who is my mother? Kirabo has been raised by women in the small village of Nattetta-her grandmother, her best friend, and her many aunts, but the absence of her mother follows her like a shadow. Complicating these feelings of abandonment, as Kirabo comes of age she feels the emergence of a mysterious second self, a headstrong and confusing force inside her at odds with her sweet and obedient nature. Seeking answers, Kirabo begins spending afternoons with Nsuuta, a local witch, trading stories and learning not only about this force inside her, but about the woman who birthed her, who she learns is alive but not ready to meet. Nsuuta also explains that Kirabo has a streak of the "first woman"-an independent, original state that has been all but lost to women. Kirabo's journey to reconcile her rebellious origins, alongside her desire to reconnect with her mother and to honor her family's expectations, is rich in the folklore of Uganda and an arresting exploration of what it means to be a modern girl in a world that seems determined to silence women. Makumbi's unforgettable novel is a sweeping testament to the true and lasting connections between history, tradition, family, friends, and the promise of a different future